Mathematics and conceptual analysis - Eagle, A (Springer Science+Business Media B.V., 2008)
Gödel argued that intuition has an important role to play in mathematical epistemology, and despite the infamy of his own position, this opinion still has much to recommend it. Intuitions and folk platitudes play a central role in philosophical enquiry too, and have recently been elevated to a central position in one project for understanding philosophical methodology: the so-called 'Canberra plan'. This philosophical role for intuitions suggests an analogous epistemology for some fundamental parts of mathematics which casts a number of themes in recent philosophy of mathematics (concerning a priority and fictionalism, for example) in revealing new light.